Perlakuan Akuntansi Syariah Berbasis Digitalisasi pada Transaksi Perbankan (Studi Kasus Bank Syariah Indonesia KCP Palembang Radial) - Yusna Putri Sidar Masek Ati; Siti Nurhayati Nafsiah (Jurusan PTIK Universitas Negeri Manado, 2026)
The rapid development of digital technology has driven significant transformation in the Islamic banking industry, including the application of sharia-based accounting practices that must remain compliant with sharia principles. The digitalization of banking transactions offers efficiency and convenience, but also presents challenges in the recognition, measurement, recording, and reporting of financial transactions in accordance with Sharia Accounting Standards (PSAK Syariah). This study aims to analyze the implementation of sharia accounting treatment based on digitalization in banking transactions at Bank Syariah Indonesia (BSI) KCP Palembang Radial, as well as to identify the challenges and efforts undertaken to maintain sharia compliance. This research employs a qualitative approach using a case study method, with data collected through interviews, observation, and documentation. The results indicate that the implementation of digital-based sharia accounting at BSI KCP Palembang Radial has been carried out properly and is in accordance with sharia principles and applicable accounting standards. Digitalization has improved transaction efficiency, accuracy of accounting records, transparency of information, and quality of customer services. However, challenges remain, particularly related to the readiness of human resources in operating digital systems. The study concludes that digitalization plays a positive role in supporting sharia accounting implementation, provided it is accompanied by continuous improvement of human resource competence and effective supervision to ensure sustained compliance with sharia principles.